2016
DOI: 10.1177/0894845316633779
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Stability and Competence in Young Adolescents’ Career Judgments

Abstract: A transition from elementary to high school represents a very profound change and a potential source of stress, as it often requires young adolescents to make significant professional decisions. This topic was the focus of the present study in which 303 Croatian students attending their final year of elementary school completed measures of career decision self-efficacy, emotional stability, emotional competence, and concerns regarding the upcoming transition. The results indicated emotional competence as a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
2
19
0
2
Order By: Relevance
“…The obtained research results corroborate this hypothesis by explaining how internalizing problems maintain an inverse relationship with social skills and EI, i.e., the higher the scores for internalizing problems, the lower the scores that adolescents obtain for performing social skills and EI, and vice versa. These results indicate how social skills and EI may act as protectors of these internalizing problems, which agrees with former research (Bubic & Ivanisevic, 2016;Martínez-Martí & Ruch, 2017;Trickey, Siddaway, Meider-Stedman, Serpell, & Field, 2012) that indicated the relationship between internalizing problems and the social competence variables. Internalizing problems (depression, anxiety, social anxiety, somatic complaints, post-traumatic symptoms, and obsession-compulsion) have been previously interrelated in recent works (Campos et al, 2014;Senzik, Shäfer, Samson, Naumann, & Tuschen-Caffier, 2017), but these works did not analyze the importance of their relationship with EI and social skills, which the present research indicates.…”
Section: Discussionsupporting
confidence: 92%
“…The obtained research results corroborate this hypothesis by explaining how internalizing problems maintain an inverse relationship with social skills and EI, i.e., the higher the scores for internalizing problems, the lower the scores that adolescents obtain for performing social skills and EI, and vice versa. These results indicate how social skills and EI may act as protectors of these internalizing problems, which agrees with former research (Bubic & Ivanisevic, 2016;Martínez-Martí & Ruch, 2017;Trickey, Siddaway, Meider-Stedman, Serpell, & Field, 2012) that indicated the relationship between internalizing problems and the social competence variables. Internalizing problems (depression, anxiety, social anxiety, somatic complaints, post-traumatic symptoms, and obsession-compulsion) have been previously interrelated in recent works (Campos et al, 2014;Senzik, Shäfer, Samson, Naumann, & Tuschen-Caffier, 2017), but these works did not analyze the importance of their relationship with EI and social skills, which the present research indicates.…”
Section: Discussionsupporting
confidence: 92%
“…This could be the reason of the Emotional Stability of the students which helped them to show positive growth rate in their educational background [38]. Also, it can be said that over a period of time, the Emotional Stability, which can be gained by stable Emotional Intelligence, has an effect on the career development of the all prospective management officials [10]. Hence, alternative hypothesis 5 can be accepted as both the tests show that the "p-value is less than the presumed alpha value".…”
Section: B Findingsmentioning
confidence: 99%
“…The career development literature has increasingly focused on the role played by emotions in the career decision-making processes (Emmerling & Cherniss, 2003, Bubić & Ivanišević, 2016, Di Fabio & Pallazzeschi, 2009, Di Fabio & Kenny, 2012, Kanonuhwa, Rungani, & Chimucheka, 2018. Bubić & Ivanišević (2016) showed that emotional competence is a significant predictor of career decision selfefficacy in eight graders. The transition to high school is associated with emotional distress related to career indecision.…”
Section: The Role Of Emotions In Vocational Orientationmentioning
confidence: 99%
“…Giving the importance of EI in obtaining success through all live, including in career (Goleman, 1985), and the first vocational choice eight graders must to do at finish of secondary school, we focused in this research on the emotional intelligence in relation with vocational interests and choices in eight graders. We focused on gender differences because literature (Bubić & Ivanišević, 2016) indicated that girls experience more concern about career choice, although they have the same level of career decision self-efficacy as boys. In line with Holland's vocational theory (1985) and Spokane et al (2002), we considered important the congruence, the consistence, and the differentiation of vocational profile for the future professional satisfaction.…”
Section: Problem Statementmentioning
confidence: 99%